Exploring the potential of village community banking as a community-based financing system for house improvements and malaria vector control in rural Tanzania. - Winifrida P Mponzi; Dickson S Msaky; Peter Binyaruka; Emmanuel W Kaindoa (Public Library of Science (PLoS), 2023)
House improvement is associated with remarkable reductions in indoor mosquito bites and disease incidences, even in typical rural houses. However, its exploitation remains extremely poor in Tanzania and other endemic countries due to limited financial resources. Nevertheless, village community banks (VICOBA), practiced in Tanzania for nearly two decades, have proven to provide financial services to rural communities that would otherwise not be able to get them from formal financial institutions. This study explored the need, opinion, and willingness of VICOBA members to use VICOBA platforms as a source of finance for improving local houses and eventually controlling mosquito-borne diseases. A mixed-methods approach was used in this study, whereby a survey was administered to 150 participants and twelve focus group discussions were done in three villages in Ulanga district, rural Tanzania. The FGDs comprised eight participants each, with equal representation of males and females. The FGD guide was used to probe the opinions of study participants on malaria transmission, housing condition improvements, and financial resources. About 99% of all participants indicated the urgent need to improve their houses to prevent mosquito bites and were willing to utilize VICOBA for improving their houses. In the focus group discussion, the majority of people who participated were also in need of improving their houses. All participants confirmed that they were at the highest risk of getting mosquito-borne diseases, and they were willing to use money that was either saved or borrowed from their VICOBA for housing improvements and vector control. A self-sustaining financial system destined for house improvement and related interventions against malaria and other mosquito-borne diseases is crucial. The community members were willing to use VICOBA as a source of finance for house improvement and disease control; however, there was limited knowledge and sensitization on how they could utilize VICOBA for disease control.